A statistical quality control study on Linkage Foods Venture Corporation - Encinas, Catherine; De La Fuente, Janelle; Madrinan, Sarah; Nepomuceno, Larissa (Diliman, Quezon City College of Engineering, 2000)
The main objective of this project study was to be able to apply Statistical Quality Control tools in analyzing the quality system of Linkage Foods Venture Corporation. Linkage Foods Venture Corporation manufactures candies, lollipops and gelatins of different flavors. The group decided to focus the study on hard candies, particularly Jolly Sampaloc and Jolly Champoy , since these comprise majority of their market share. The research process included plant visits and interviews with key personnel. Historical data were gathered and analyzed using Streamline Diagnostic Analysis, Ishikawa Diagrams, Failure Mode Effects and Analysis (FMEA), and Control Charts. The quality problems identified were the melting of candies before expiration date due primarily to high moisture content and the deformed or broken candies. The control charts were used to analyze the processes involved in the production of hard candies. From the charts, it was seen that the processes were in-control so the group recommended the company to maintain that. Process capability analysis was also conducted and it showed that the process for determining the moisture content of the candies is capable of producing products within the specifications while the process of controlling the humidity of the cold room is incapable. The group formulated recommendations including the addition of an additional enclosure made of curtain-like plastic in the entrances of the cold room, quality control training for management and workers of Linkage Foods, and the use of forms for monitoring purposes like the check sheet for the deformed candies.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Linkage Food Venture Corporation; Food industry; Quality control